2020
DOI: 10.1177/0964528420912259
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acupuncture on anthropometric and serum metabolic parameters in premenopausal overweight and obese women: a randomized, patient- and assessor-blind, sham-controlled clinical trial

Abstract: Objective: The aim of this study was to examine the effect of acupuncture on obesity-related parameters with regard to metabolomics. Methods: This two-arm parallel, patient- and assessor-blind, sham-controlled randomized clinical trial included 120 obese participants. Participants were randomized into two groups. The treatment group received a combined intervention of manual acupuncture (MA) plus electroacupuncture (EA), while the control group received a combination of sham acupuncture interventions consistin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
1
5
0
1
Order By: Relevance
“…23 A similar study was conducted by Kim et al and demonstrated that manual acupuncture plus electroacupuncture treatment led to weight loss in obese participants and the HDL cholesterol levels significantly increased. 24 Our new findings in this study were in agreement with previous studies in terms of the reduction effect of acupuncture treatment on TC and LDL cholesterol levels.…”
Section: Discussionsupporting
confidence: 93%
“…23 A similar study was conducted by Kim et al and demonstrated that manual acupuncture plus electroacupuncture treatment led to weight loss in obese participants and the HDL cholesterol levels significantly increased. 24 Our new findings in this study were in agreement with previous studies in terms of the reduction effect of acupuncture treatment on TC and LDL cholesterol levels.…”
Section: Discussionsupporting
confidence: 93%
“…When manual acupuncture + electroacupuncture is applied to the acupoint, certain carnitine (L2, L4, L6 and L-Carnitine) levels significantly increased, compared to the sham acupuncture group [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The 13 selected studies [24][25][26][27][28][29][30][31][32][33][34][35][36] were analyzed based on the authors' names, publication year, study design, number of participants in each group, details of the experimental and control groups, duration and frequency of treatment, outcome measures, and adverse effects (Table 2). The selected studies were published between 2005 and 2021, with 8 studies written in English and 5 in Chinese.…”
Section: Study Characteristicsmentioning
confidence: 99%